Comorbidity between epilepsy and depression: Experimental evidence for the involvement of serotonergic, glucocorticoid and neuroinflammatory mechanisms - Pineda, Eduardo (2010)
Depression represents one of the most common comorbidities of temporal lobe epilepsy (TLE), and has profound negative impact on the quality of life of TLE patients. However, causes and mechanisms of depression in TLE remain poorly understood, and its effective therapies are lacking. We examined whether a commonly used model of TLE in rats can be used as a model of comorbidity between epilepsy and depression suitable for both mechanistic studies and for the development mechanism-based antidepressant therapies. We established that animals which had been subjected to LiCl and pilocarpine status epilepticus (SE) and developed spontaneous recurrent seizures, exhibited set of impairments congruent with depressive state: behavioral equivalents of anhedonia and despair; dysregulation of the hypothalamo-pituitary adrenocortical (HPA) axis; compromised raphe-hippocampal serotonergic transmission. Pharmacological studies suggested that depressive impairments following SE develop as a result of the enhanced interleukin-1β signaling in the hippocampus, which leads to depression via inducing perturbations in the HPA axis and subsequent deficit in the raphe-hippocampal serotonergic transmission.